2002
DOI: 10.1016/s0014-5793(02)03305-7
|View full text |Cite
|
Sign up to set email alerts
|

Dominant negative mutant of a lipoprotein‐specific molecular chaperone, LolA, tightly associates with LolCDE

Abstract: Periplasmic molecular chaperone LolA and the inner membrane ATP binding cassette transporter LolCDE are essential for ATP-dependent release of outer membrane-directed lipoproteins from the inner membrane of Escherichia coli. A LolA(F47E) mutant carrying a Phe to Glu mutation at position 47 was defective in the release of lipoproteins from spheroplasts and proteoliposomes reconstituted with LolCDE. When incubated with proteoliposomes containing LolCDE, LolA remained in the supernatant whereas LolA(F47E) bound t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2004
2004
2018
2018

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 17 publications
(44 reference statements)
0
17
0
Order By: Relevance
“…These proteins may play many roles in oxidation or reduction pathways in the cytoplasmic membrane or periplasmis space, similar to the Dsb proteins in E. coli (31). The observation that the gene encoding LolA, a prokaryotic periplasmic lipoproteinspecific molecular chaperone (27,28), is cotranscribed with trxB in an operon regulated by oxidative and thiol redox stress supports the idea that some of these proteins are localized in the periplasm and membrane of this anaerobe. Further studies should help us to clarify how B. fragilis TrxB, the Trxs, and thiol disulfide oxidoreductase-like proteins are employed to reduce different cytoplasm and periplasm substrates in an anaerobic organism.…”
Section: Discussionmentioning
confidence: 69%
“…These proteins may play many roles in oxidation or reduction pathways in the cytoplasmic membrane or periplasmis space, similar to the Dsb proteins in E. coli (31). The observation that the gene encoding LolA, a prokaryotic periplasmic lipoproteinspecific molecular chaperone (27,28), is cotranscribed with trxB in an operon regulated by oxidative and thiol redox stress supports the idea that some of these proteins are localized in the periplasm and membrane of this anaerobe. Further studies should help us to clarify how B. fragilis TrxB, the Trxs, and thiol disulfide oxidoreductase-like proteins are employed to reduce different cytoplasm and periplasm substrates in an anaerobic organism.…”
Section: Discussionmentioning
confidence: 69%
“…Previous biochemical data (13,15) have suggested that differences in the affinity for lipoproteins drive the transport of lipoproteins to the outer membrane via LolB. The crystal structures of LolA and LolB (18), and the phenotypes of LolA mutants, R43L (19) and F47E (20), indicated the importance of opening and closing of the LolA lid for lipoprotein binding to LolA, and subsequent lipoprotein transfer from LolA to LolB, respectively (Fig. 7A).…”
Section: Discussionmentioning
confidence: 73%
“…X 1 -X 3 and X 4 -X 6 for the respective derivatives are shown above. Construction of R43L (19) and F47E (20) was reported previously. Although not reported, the F47D, F47K, and F47P mutants have previously been isolated in addition to F47E by means of random mutagenesis.…”
Section: Construction Of Lola Mutants As To Arg At Position 43 and Phmentioning
confidence: 99%
See 1 more Smart Citation
“…The replacement of Phe at position 47 with Glu gave a dominant negative LolA derivative, which cannot accept lipoproteins and remains tightly associated with LolCDE (17). Since Phe 47 is one of the residues forming the hydrophobic cavity (Fig.…”
mentioning
confidence: 99%